Development of upper and lower extremity functional asymmetries in male and female elite youth tennis players: a longitudinal study - Chapelle, L.; Bishop, C.; D`Hondt, J.; Rommers, N.; D`Hondt, E.; Clarys, P. (The Journal of Sports Medicine and Physical Fitness, 2023)
BACKGROUND: This longitudinal study aimed to examine the development of both upper and lower extremity functional performances, together with asymmetry magnitudes and directionality in youth tennis players. METHODS: Dominant and non-dominant physical performance values of 90 players (53 males, 37 females) were determined yearly (with monitoring up to 3 years) using unilateral strength, power, speed and agility tests from which asymmetry magnitude percentages were calculated. Linear mixed effect models examined the development of performance values according to youth players` maturity offset, performance dominance, sex and training volume. Similarly, the development of functional asymmetry magnitudes was examined according to players` maturity offset, sex and training volume. Kappa coefficients (k) examined the consistency in directionality across test occasions. RESULTS: Regardless of sex, the dominant and non-dominant physical performance values of every test significantly (P<0.05) improved with increasing maturity offset. No sex differences were apparent except for strength and power related tests where male players performed significantly better. Functional asymmetry magnitudes (ranging from 2.0 to 15.9%) did not significantly change with increasing maturity offset (range=-0.3-0.4% per year). Training volume was not significantly associated with the performance values and asymmetry magnitudes. The dominant upper extremity (which holds the tennis racket) consistently displayed the dominant performance value (k value: 1.00) across test occasions, which was not the case at lower extremity level (k value range: -0.28-0.31). CONCLUSIONS: The functional asymmetry magnitudes did not change significantly with youth tennis players` maturity offset over a 3-year period.